A double-controller fuzzy scheme for intelligent resource discovery on IaaS cloud systems. (17th June 2021) - Gharajeh, Mohammad Samadi; Jahangir, Babak
The resource discovery process discovers appropriate computing resources (e.g., shared memory) in infrastructure as a service (IaaS) cloud systems according to user requirements. Since fuzzy systems use intelligent procedures based on humanistic experiences, they can be used in cloud computing to increase the number of completed jobs and improves the success rate. This paper proposes a double-controller fuzzy scheme for intelligent resource discovery in IaaS cloud systems, called DOCFIR. This scheme applies two fuzzy controllers to perform the intelligent resource discovery across the network. The first controller determines the number of virtual machines in the deployment phase based on the most important characteristics of the physical machines. The second controller discovers the appropriate computing resources for the user's job in the service phase based on characteristics of the physical machines and user requirements. The simulation results show that the proposed scheme surpasses some of the existing related works in terms of the number of completed jobs and success rate.